Analysis of battery energy storage system (BESS) performance in reducing the impact of variable renewable energy generation intermittency on the electricity system - Mudakir, Mudakir; Aripriharta, Aripriharta; Wibawa, Aji Prasetya (Journal of Mechatronics, Electrical Power, and Vehicular Technology, 2024)
Indonesia has set a target to achieve a 23 % share of new and renewable energy (NRE) in its national energy mix by 2025. Sulawesi island has significant wind and solar energy potential, but the integration of these variable renewable energy (VRE) sources, such as solar photovoltaic (PV) and wind turbines (WT), poses challenges due to their fluctuating output. The aim of this study is to analyze the impact of battery energy storage systems (BESS) in reducing the intermittency of solar power generation and improving grid stability in North Sulawesi and Gorontalo. The study uses a combination of various technical simulations to assess the performance of BESS in stabilizing voltage and frequency fluctuations within the electricity system. The approach includes power flow analysis, transient stability testing, and short-circuit studies, with and without the integration of BESS. The results show that implementing a 10 MW/5 MWh BESS can significantly reduce frequency deviations, limiting frequency drops to 49.82 Hz during disturbances, compared to 49.67 Hz without BESS. In addition, BESS helps maintain voltage stability at critical substations by reducing voltage fluctuations by up to 40 %. This research demonstrates that BESS integration can enable a more stable and reliable grid, supporting the development of renewable energy without compromising power quality.